Serology of Viral Infections and Tuberculosis Screening in an IBD Population Referred to a Tertiary Centre of Southern Italy - Marco Ardesia; Giuseppe Costantino; Placido Mondello; Angela Alibrandi; Walter Fries (Gastroenterology Research and Practice)
Background. With the introduction of more potent immunosuppressive agents in inflammatory bowel disease, prevention of opportunistic infections has become necessary by introducing screening programs. Prevalence of the most important infectious agents may vary in different geographical areas. The aim of our study was to assess the immune status for hepatitis B, varicella, mononucleosis, and cytomegalovirus infection together with the determination of the hepatitis C and tuberculosis status in Southern Italy. Methods. Prevalence of latent tuberculosis, together with serology of hepatitis B and C, Epstein-Barr virus, varicella zoster, and cytomegalovirus were collected by analysing retrospectively the clinical charts of IBD patients. Data were integrated with demographic and clinical features. Results. Data from 509 IBD patients divided in two age groups showed a prevalence of HBV infection in nonvaccinated patients of 9%. Seroprotection (HBsAb) in vaccinated IBD patients was lower (p<0.0001) compared with that in controls. Prevalences of herpesvirus infections fluctuate between 51% (CMV) and 85% (EBV) and 84% (VZV) in younger patients. Latent tuberculosis and hepatitis C infection were found only in patients > 37 years of age. Conclusions. In younger patients, high susceptibility rates for primary herpesvirus infections should determine the choice of treatment. Loss of HBV seroprotection in already vaccinated patients should be considered for booster vaccination programs.